Rural vs Urban: Teachers' Obstacles and Strategies in Mathematics Learning During COVID-19 Pandemic - Fadhil Zil Ikram; Rosidah Rosidah (Southeast Asian Mathematics Education Journal, 2020)
During the pandemic of COVID-19, numerous obstacles arose in education, and some strategies were necessary to tackle them. This study adopted a qualitative approach to investigate teachers' difficulties in mathematics learning in rural and urban areas and how they solved them. The findings revealed that motivation, productivity, and activityare the main problems of the teachers. Accessibility also poses a difficulty for teachers in rural areas. Several strategies were implemented to solve these obstacles, including using technology, maintaining communication with families, providing flexibility, reducing the number of tasks and quizzes, and peer teaching.